Identificación de un mercado potencial para la exportación de mermelada de guayaba (2022)
The objective of this document is to identify the potential markets for the export of guava. At the methodological level, a descriptive with a mixed approach is used, using the documentary review of research on the study of marmalade exports, foreign trade databases and official reports. The results made it possible to show that jam is a product with high demand worldwide, with countries such as Germany, the United States, the United Kingdom, among others, being the main importers. The easy conservation of the product, its flavor, as well as its nutritional content make it highly demanded in homes, which is consumed directly or as an ingredient for other preparations. Considering the main importers and the trade agreements that Colombia has with them, three objective countries were considered: the United States, Germany and France. Through a market selection matrix, aspects of foreign trade, demographic data, trade relations, taxes, among others, were assessed. The selection showed that the potential market is Germany, which has a high consumption, its population has a high purchasing power and exports are facilitated considering the free market agreement with Europe. It is concluded that Germany is a potential market that offers profitability for the export of guava jam. To consolidate the opportunities that this offers, some aspects of the logistics to export to this country are presented.